Relationship Between Family Income And Stunting Incidence For Toddlers In Banjarsari Wetan Village In 2023 - Noviansari, Revita Dwi; Ramadanintyas, Karina Nur; Abidin, Zaenal (International Journal of Health Literacy and Science, 2023)
Stunting is a condition where there is a failure of growth and development in children under five which is triggered by malnutrition. Based on data it was recorded that in 2021 there were 195 toddlers who were stunted, while in 2022 there were 69 (30.39%) toddlers who were stunted. The aim of the study was to determine the relationship between family income and the incidence of stunting in toddlers in the Banjarsari Wetan village. This research uses analytical survey methods with case control approach. The The sample for this research is 60 respondents (30 cases and 30 controls). Data analysis used is univariate analysis, bivariat uses test chi square. The results showed that the most dominant sex of toddlers was male, which was 60%, while family income in Banjarsari Wetan Village was high income (51.7%). The results of the chi square test analysis were obtained (p = 0.002) which means that there is a relationship between family income and the incidence of stunting in toddlers in Banjarsari Wetan Village. The conclusion from this study is that there is a relationship between family income with the incidence of stunting.